Profiling consumers with an environmentally sustainable and healthy diet: The case of Spanish households - Gutiérrez-Villar, Belén; Melero-Bolaños, Rosa; Montero-Simo, Maria Jose; Araque-Padilla, Rafael A. (Frontiers in Nutrition, 2022)
Our diet has substantial implications not only for our health but also for the environment. However, the two dimensions are not comparable, even though consumers often associate them with their purchasing choices. Promoting more sustainable diets requires a better knowledge of household profiles considering the healthy and organically sustainable character of the food purchased. Previous studies have approached the analysis of consumer profiles separately, differentiating both dimensions without clear conclusions regarding the variables that make up these profiles. In this study, we looked for household profiles by cross-referencing the organic nature of the products consumed (environmental sustainability) with their degree of processing (healthfulness) in Spain. The results show that the most sustainable products are consumed in tiny municipalities (less than 2,000 inhabitants). In contrast, less sustainable products are consumed in high-income, single-family households or households with small children. The person responsible for the purchase is working or between 39 and 45 years old. In conclusion, our study shows that socio-demographic variables are statistically significant in identifying household profiles with sustainable diets.